Synthetic fiber "Teddy Bear" conjunctival granuloma; A case report - Roshanak Aliakbar-Navahi; Mohammad Hossein Roozitalab; Mohammad Javad Ashraf; Afsoon Hakimzadeh (Journal of Ophthalmic & Vision Research, 2015)
Purpose: To report the clinicopathologic features of a case of conjunctival synthetic fiber granuloma. Case Report: A 6-year-old girl presented with a slow-growing red nodule in the right inferior conjunctival sac with no history of surgery or trauma. Histopathological examination revealed foreign body type granulomatous inflammation around birefringent fibers of variable colors consistent with synthetic fiber granuloma. Conclusion: This is the first case report of synthetic fiber (teddy bear) conjunctival granuloma from Iran. Despite its scarcity, ophthalmologists should consider this type of granuloma in the differential diagnoses of childhood conjunctival lesions especially when the lesion is unilateral and inferior.